2019
DOI: 10.2478/jvetres-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective liver histomorphological analysis in dogs in instances of clinical suspicion of congenital portosystemic shunt

Abstract: Introduction: The clinical symptoms of portosystemic shunts (PSSs) and hepatic microvascular dysplasia (HMD) – portal vein hypoplasia (PVH) in dogs are similar. PSSs are abnormal vascular connections between the portal vein system and systemic veins. HMD is a very rare developmental vascular anomaly, recognisable during histopathological examination. The study aim was to assess the prevalence of HMD–PVH and hepatocellular and vascular pathologies in the liver. Material and Methods: Liver biopsies from 140 dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, some dogs included in our study had a later presentation, supporting the idea that the onset of clinical signs may occur at any age [ 1 ]. The majority of the dogs were diagnosed with an extrahepatic PSS, a more common finding in smaller breeds [ 35 ], which comprised the majority of our study population. Agreeing with many reports, most dogs had a typical presentation, including neurological (at 78% being the most common sign in our study), GI, and urological signs.…”
Section: Discussionmentioning
confidence: 99%
“…However, some dogs included in our study had a later presentation, supporting the idea that the onset of clinical signs may occur at any age [ 1 ]. The majority of the dogs were diagnosed with an extrahepatic PSS, a more common finding in smaller breeds [ 35 ], which comprised the majority of our study population. Agreeing with many reports, most dogs had a typical presentation, including neurological (at 78% being the most common sign in our study), GI, and urological signs.…”
Section: Discussionmentioning
confidence: 99%
“…As portal fibrosis development along with other pathological histomorphological hepatic changes is suggested to be associated with prolonged shunt patency and MAPSS ( 4 6 ), it would be expected for MAPPS dogs to have increased liver stiffness which might be demonstrated with non-invasive 2D SWE ( 2 , 33 , 39 ). Tamura et al in their recent study showed the correlation between liver stiffness and the clinical stage of hepatic fibrosis in dogs ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liver histology of dogs suffering from congenital PSS demonstrates many changes such as microscopic bile duct proliferation, hypoplasia of portal tributaries, arteriolar proliferation, and smooth muscle hypertrophy, with some dogs also showing evidence of fibrosis ( 4 , 5 ). In one recent study, some degree of liver fibrosis was present in about 90% of dogs with congenital extrahepatic PSS (EHPSS), with some even categorized as an advanced stage of fibrosis ( 6 ). The degree of portal fibrosis has been suggested to increase with advanced age with a resolution of hepatic changes in dogs with closed EHPSSs ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of the MAPSSs was classified as microvascular dysplasia or portal vein hypoplasia if results of histologic examinations performed by a board-certified veterinary pathologist were available for review and documented compatible findings, including arteriolar duplication and reduplication, portal endothelial hyperplasia, portal hypoperfusion, and portal venous hypoplasia. 35,36 Other hepatic histologic abnormalities were classified separately as listed in the medical records as cirrhosis, hepatitis, copper hepatopathy, lipogranulomas, and fibrosis. Dogs with evidence of multiple hepatic abnormalities were assigned to all qualified groups.…”
Section: Medical Records Reviewmentioning
confidence: 99%